Analysis of Indonesian Spelling Errors in Academic Texts Critical Book Review (CBR) Students of the Physics Departement,Medan State University - Sihombing, Lince Hartanti; Dina Khotipah Batubara; Kelsri Ivana Belinda; Renita Gustriana Siallagan; Lasenna Siallagan; Sarah Miranda Gultom (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze spelling errors in the academic texts of Physics Department students at Medan State University, especially in Critical Book Review (CBR) papers). The research method applied is descriptive analysis, using two CBR papers obtained from students with different study program backgrounds. The research results showed that there were various language errors, including word writing errors, capital letter errors, italic writing errors and punctuation errors that were not in accordance with EBI standards. The implication of these findings is the potential to improve learning strategies that are more effective in honing students' abilities in writing academic texts that are good and according to the rules. With a deeper understanding of frequently occurring errors, it is hoped that students' linguistic proficiency in academic writing will improve